Sozialkapital zur Sprache gebracht eine bedeutungstheoretische Perspektive auf ein sozialwissenschaftliches Begriffs- und Theorieproblem - Koob, Dirk (Universitätsverlag Göttingen, 2007)
The term "social capital" has become a buzzword with a huge, already diffuse spectrum of application. This should give reason for conceptual and theoretical vigilance. What - in concrete - is the object when "social capital" is mentioned? This question has not been systematically dealt with and even less responsed in a satisfactory degree, although there are many contributions to the discussion of the term. The problem is labelled in the social sciences, but has not been resolved in the context of the specific social-scientific framework. This book takes the neglected metalinguistic perspective. Thus it advances the scientific maturity of the "social capital" debate and contributes to the establishment of a well-founded system in social science terms. It brings up social capital by combining an epistemological and ontological analysis and thus finally develops clarification of the concept.